Stent thrombosis with ticagrelor versus clopidogrel in patients with acute coronary syndromes - Steg, P. Gabriel; Harrington, Robert A.; Emanuelsson, Håkan; Katus, Hugo; Mahaffey, Kenneth W.; Meier, Bernhard; Storey, Robert F.; Wojdyla, Daniel M.; Lewis, Basil S.; Maurer, Gerald; Wallentin, Lars; James, Stefan K. (Circulation, 2013)
Background— - - We aimed to describe the effects of ticagrelor versus clopidogrel on stent thrombosis in the Platelet Inhibition and Patient Outcomes (PLATO) trial. - - Methods and Results— - - Of 18 624 patients hospitalized for acute coronary syndromes, 11 289 (61%) had at least 1 intracoronary stent. Ticagrelor reduced stent thrombosis compared with clopidogrel across all definitions: definite, 1.37% (n=71) versus 1.93% (n=105; hazard ratio [HR], 0.67; 95% confidence interval [CI], 0.50-0.90; P=0.0091); definite or probable, 2.21% (n=118) versus 2.87% (n=157; HR, 0.75; 95% CI, 0.59-0.95; P=0.017); and definite, probable, and possible, 2.94% (n=154) versus 3.77 (n=201; HR, 0.77; 95% CI, 0.62-0.95). The reduction in definite stent thrombosis was consistent regardless of acute coronary syndrome type, presence of diabetes mellitus, stent type (drug-eluting or bare metal stent), CYP2C19 genetic status, loading dose of aspirin, dose of clopidogrel before randomization, and use of glycoprotein IIb/IIIa inhibitors at randomization. The reduction in stent thrombosis with ticagrelor was numerically greater for late (>30 days; HR, 0.48; 95% CI, 0.24-0.96) and subacute (4 hours-30 days; HR, 0.60; 95% CI, 0.39-0.93) compared with acute (<24 hours; HR, 0.94; 95% CI, 0.43-2.05) stent thrombosis or for patients compliant to therapy (ie, taking blinded study treatment ≥80% of the time) compared with less compliant patients. Randomization to ticagrelor was a strong independent inverse predictor of definite stent thrombosis (HR, 0.65; 95% CI, 0.48-0.88). - - Conclusion— - - Ticagrelor compared with clopidogrel reduces the incidence of stent thrombosis in patients with acute coronary syndromes, with consistent benefit across a broad range of patient, stent, and treatment characteristics. - - Clinical Trial Registration— - - URL: http://www.clinicaltrials.gov. Unique identifier: NCT00391872.
Gesehen am 15.02.2022